Aerobna zmogljivost oseb po hudi nezgodni možganski poškodbi - Ščavničar, Ana (Rehabilitacija (Ljubljana), 2015)
Background After traumatic brain injury (TBI), people often show low tolerance to sustained physical activity. The degree of aerobic capacity limitation in recovering TBI patients is not well documented. Additionally, people with TBI often report fatigability, which could also have an impact on reduced aerobic capacity. The aim of our study was to compare the aerobic capacity of subjects after TBI with the aerobic capacity of healthy individuals, to determine the influence of fatigue on reduced aerobic capacity and to evaluate the suitability of the modified Balke-Ware protocol for testing persons after TBI. Subjects and methods We included 18 participants, 9 patients after severe traumatic brain injury and 9 healthy volunteers (matched by sex and age). Patients after TBI were evaluated with the Fatigue Severity Scale (FSS) prior to testing. The participants were tested on a treadmill. We followed the criteria advised for maximal testing. The test was conducted according to a modified Balke-Ware protocol. The protocol consists of 8 levels: during testing the treadmill speed remains constant (5.3 km/h) and the slope gradually increases by 2% every 2 minutes until it reaches 14% at the eight level. During the test, ECG, heart rate (HR), oxygen consumption (VO2), minute ventilation (VE), and the respiratory exchange ratio (RER) were continuously observed and measured. Based on the data collected, oxygen pulse (O2/p) and the ventilatory equivalents for oxygen (VE/VO2) and carbon dioxide (VE/CO2) were calculated. Results All the participants achieved more than 36 points on the FSS. All the participants except one reached one of the final two exercise test levels. There were no complaints during the testing. We did not observe any safety risks or medical problems. The participants in the test group completed the test with a heart rate averaging 83% of the age-predicted heart rate, an average RER of 1.1 and an average VO2 of 30.4 ml/kg/min. The healthy volunteers completed the test with a heart rate averaging 89% of the age-predicted heart rate, an average RER of 1.0 and an average VO2 of 33.3 ml/kg/min. No statistically significant differences between the two groups were found. Conclusions Reduced aerobic capacity is not linked to the fatigability reported after traumatic brain injury. The modified Balke- Ware protocol is a safe method for testing the aerobic capacity of persons after traumatic brain injury.
Keywords: aerobic capacity; aerobna zmogljivost; Brain Injuries; fatigability; nezgodna možganska poškodba; traumatic brain injury; utrudljivost